Facilitators and barriers to implementing clinical care pathways - Evans-Lacko, Sara (BioMed Central, 2010)
BACKGROUND: The promotion of care pathways in the recent Governmental health policy reports of Lord Darzi is likely to increase efforts to promote the use of care pathways in the NHS. Evidence on the process of pathway implementation, however, is sparse and variations in how organisations go about the implementation process are likely to be large. This paper summarises what is known about factors which help or hinder clinicians in adopting and putting care pathways into practice, and which consequently promote or hinder the implementation of scientific evidence in clinical practice. DISCUSSION: Care pathways can provide patients with clear expectations of their care, provide a means of measuring patient's progress, promote teamwork on a multi-disciplinary team, facilitate the use of guidelines, and may act as a basis for a payment system. In order to achieve adequate implementation, however, facilitators and barriers must be considered, planned for, and incorporated directly into the pathway with full engagement among clinical and management staff. Barriers and/or facilitators may be present at each stage of development, implementation and evaluation; and, barriers at any stage can impede successful implementation. Important considerations to be made are ensuring the inclusion of all types of staff, plans for evaluating and incorporating continuous improvements, allowing for organisational adaptations and promoting the use of multifaceted interventions. SUMMARY: Although there is a dearth of information regarding the successful implementation of care pathways, evidence is available which may be applied when implementing a care pathway. Multifaceted interventions which incorporate all staff and facilitate organisational adaptations must be seriously considered and incorporated alongside care pathways in a continuous manner. In order to better understand the mechanism upon which care pathways are effective, however, more research specifically addressing conditions under which providers become engaged in using care pathways is needed.